Gastrointestinal helminths of Emperor Penguin (Aptenodytes forsteri) from Antarctica - Fusaro, Bruno; Libertelli, Marcela; Ansaldo, Martin; Coria, Néstor Rubén; Diaz, Julia Inés (Polar Biology)
Although research on parasitic diseases in Antarctic birds is scarce and the information largely fragmented, an increasing number of studies are currently in progress in this area. The host/parasite relationship is very important for understanding the impact of parasitism on the seabirds’ feeding ecology, especially in those isolated regions where the host is extremely sensitive to new diseases. Penguins are a big favorite for these studies because of their importance as indicators of change in the Antarctic ecosystem. This study aims at adding information on gastrointestinal parasites of the Emperor Penguin Aptenodytes forsteri from Snow Hill colony. Based on a sample of 43 individuals found freshly dead (3 adults and 40 chicks) from predation or starvation, the gastrointestinal helminth community in Emperor penguins was composed of two species of cestodes (Parorchites zederi and Tetrabothrius sp.) and three species of nematodes (Stegophorus macronectes, Tetrameres sp. and Contracaecum osculatum). This is the first record of S. macronectes in the Emperor Penguin. The low parasite richness observed might be related to the stenophagic and pelagic diet of this host. Fil: Fusaro, Bruno. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios Parasitológicos y de Vectores; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Libertelli, Marcela. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Ansaldo, Martin. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: ...